2021
DOI: 10.25105/jmpj.v14i1.8541
|View full text |Cite
|
Sign up to set email alerts
|

How to encourage lecturer performance in research through servant leadership, organizational commitment, and tacit knowledge sharing

Abstract: <p>The purpose of the present study was to analyze the role of servant leadership, organizational commitment, and tacit knowledge sharing in enhancing research performance. To this end, a survey of 400 randomly recruiting private university lecturers was conducted. The data were analyzed by using SEM covariant. The analysis result showed that leadership that tends to exhibit service and sacrifice towards its subordinate improved organizational commitment, particularly in the continuance and normative dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Lee, Lyubovnikova [ 13 ] systematic review concludes that SL has the characteristics to satisfy subordinates based on emotional, ethical, spiritual, and relational grounds. According to Hoch, Bommer [ 40 ], the empirical power of SL is higher than other positive leadership styles, and it has emerged as one of the most important leadership styles for producing numerous positive outcomes including improving employees’ commitment [ 41 ], engagement [ 42 ], motivation and job performance [ 43 ], creativity and innovations [ 44 ], work-related wellbeing [ 45 ], innovative work behavior [ 46 ], citizenship behaviors [ 47 ], positive deviance [ 48 ], productive voice behavior [ 49 ] and pro-social behaviors [ 50 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Lee, Lyubovnikova [ 13 ] systematic review concludes that SL has the characteristics to satisfy subordinates based on emotional, ethical, spiritual, and relational grounds. According to Hoch, Bommer [ 40 ], the empirical power of SL is higher than other positive leadership styles, and it has emerged as one of the most important leadership styles for producing numerous positive outcomes including improving employees’ commitment [ 41 ], engagement [ 42 ], motivation and job performance [ 43 ], creativity and innovations [ 44 ], work-related wellbeing [ 45 ], innovative work behavior [ 46 ], citizenship behaviors [ 47 ], positive deviance [ 48 ], productive voice behavior [ 49 ] and pro-social behaviors [ 50 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Hence, it is a unique leadership style and thereby followers may feel to reciprocate the gesture. Therefore, it is no surprise that researchers have studied servant leadership together with job satisfaction (Hasanuddin, Mustainah, & Buntuang, 2021), organizational commitment (Winarno, & Hermana, 2021) and employee performance (Sarwar, Cavaliere, Ammar, & Afzal, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, 2020; Kelloway and Barling, 2000; Rehman et al. , 2020; Smith and McKeen, 2002; Van Den Hooff and De Ridder, 2004; Vu and Yazdani, 2021; Wiarno and Hermana, 2021) are limited and have not depicted a distinctive picture that could be beneficial for practice. For example, Costa and Monterio (2012) tested the relationship between the three components of organisational commitment and KS, including information donation and collection, in universities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Vu and Yazdani (2021) reported a positive impact of organisational commitment on KS amongst 500 lecturers in Vietnamese universities. Further, in a study conducted on 400 private university lecturers in Indonesia, Wiarno and Hermana (2021) concluded that tacit KS is affected by organisational commitment in terms of the research performance of faculty.…”
Section: Introductionmentioning
confidence: 99%